Immigration and natives' task specialization - Kim, Hyejin,Lee, Jongkwan (Bank of Korea, 2022)
While imperfect substitutability between native and immigrant workers is one of the important mechanisms in estimating the wage effects of immigration, its empirical literature is concentrated on the context of only a few countries. Using occupation task-intensity data from a unique Korean dataset, we demonstrate that native Korean workers respond to increased immigration by pursuing jobs more intensive in communication tasks. This result explains how task specialization from immigration could be a general pattern across countries
10.2139/ssrn.4001098
Keywords: Graue Literatur; Immigration; Task specialization; Native workers; South Korea